REVITALISASI PERPUTAKAAN DESA UNTUK PENINGKATAN LITERASI ANAK MELALUI KKM TEMATIK LITERASI DI DESA MEKARSARI - Dinar Nirmalasari (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
Thematic Literacy Student Community Service Program (KKM) of Group 35, Sultan Ageng Tirtayasa University, was implemented from July 8 to August 7, 2025, at the Sumber Ilmu Library, Mekarsari Village, Rajeg Subdistrict, Tangerang Regency. This activity aimed to revitalize the function of the village library as a literacy center and to improve the reading skills of elementary school students. The implementation method employed a participatory approach through coordination with schools, library managers, the village government, and the community. The main programs included Read Aloud, Read Me a Book, Smart Book Review, Book-Based Project and Story Creation, and Village-Level Literacy Appreciation. Supporting programs comprised reading tutorials, creative competitions, healthy exercise sessions, and communal work (gotong royong). The results indicated increased participation of students from SDN Sukasari 2, enhanced creativity, and strengthened communication skills through storytelling competitions. Program sustainability was achieved through the commitment of village youth volunteers to continue weekly reading tutorials and the routine scheduling of healthy exercise sessions by the karang taruna (youth organization). In conclusion, the revitalization of the village library through the Thematic Literacy KKM has proven effective in fostering reading interest, creativity, and social interaction among children, while simultaneously reinforcing the library’s role as an active community learning center.Keywords: Literacy; Village Library; Community Service; KKM; UNTIRTA